3.7 Mb tandem microduplication in chromosome 5p13.1-p13.2 associated with developmental delay, macrocephaly, obesity, and lymphedema: further characterization of the dup(5p13) syndrome - Oexle, Konrad; Hempel, Maja; Jauch, Anna; Meitinger, Thomas; Rivera-Brugués, Núria; Stengel-Rutkowski, Sabine; Strom, Tim (European journal of medical genetics, 2011)
In a male patient with developmental delay, autistic behaviour, obesity, lymphedema, hypertension, macrocephaly, and facial features of chromosome 5p duplication (trisomy 5p) a 3.7 Mb de novo tandem microduplication of 5p13.1-13.2 (rs4703415-rs261752, i.e., chr5:35.62-39.36 Mb) was identified. This observation contributes to the characterization and dissection of the 5p13 duplication syndrome. The possible role of increased NIPBL gene dosage is discussed.
Gesehen am 29.09.2022